Anthropometric indicators of obesity. Are the new indicators a better predictor of body fat content than BMI? - Teresa Walczyk (Kazimierz Wielki University, 2021)
Anthropometric measurements are widely used in medicine, scientific research, but also in specialist medical care. Their proper use provides valuable information about the nutritional status, the adipose tissue and even the risk of comorbidities. Numerous scientific works question the usefulness of the BMI (body mass index), which is only an indirect measure of obesity. It does not take into account information on gender and age, and does not provide an answer on the distribution of body fat. Misclassification can result in serious deviations in the estimation of obesity-related effects. Therefore, the aim of this study is to present five new anthropometric obesity indicators as an alternative to BMI. In response to the dramatically growing problem of overweight and obesity, further exacerbated by the necessary restrictions related to the COVID-19 pandemic, it is necessary to search for precise, yet simple tools for assessing body composition that can be routinely used by individuals but also for population studies. Based on the literature review, five frequently described indicators were selected: Relative Fat Mass (RFM), A Body Shape Index (ABSI), Body Adiposity Index (BAI), Body Roundness Index (BRI) and CUN-BAE. Application possibilities and their effectiveness for the estimation of adipose tissue content and the risk of coexisting diseases are presented. Growing number of authors confirm the validity of using indicators such as RFM, BRI, CUN-BAE and ABSI. At the same time, researchers point to the need for further verification of their usefulness in clinical practice and public health.